EVALUASI PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA DAN IMPLEMENTASI KEGIATAN TENAGA KESEHATAN BERSINERGI BERSAMA UNTUK MASYARAKAT SEHAT - asma suhada; Arif Budiwitarto; Zulkieflimannsyah Zulkieflimannsyah; Mukhammad Najib; Kahar Karim (Distribusi - Journal of Management and Business, 2020)
Indonesia Program, increase awareness, willingness, and ability to live healthy lives for everyone to improve their health status as high as possible. The healthy Indonesia program with a family approach is an effort to respond to these health development challenges. The results of the Healthy Indonesia Family Approach Program will be one of the references in planning the management of health centers. This study was to observe the implementation of the Healthy Indonesia Program with the Family Approach and the performance of TAKASIMURAH at The Health Center of Labuhan Badas District. The method used is descriptive qualitative data collection techniques as interviews, observation, and study of documents. The results show, the Healthy Indonesia Program activities with the Family Approach optimally implemented, and the performance of TAKASIMURAH was able to increase program achievements according to 12 indicators set. The results of this study are expecting to be a reference by other health centers in improving services using the same innovation.